Comprehensive genome-wide analysis of the HMGR gene family of Asparagus taliensis and functional validation of AtaHMGR10 under different abiotic stresses - Zeng, Liangqin; Brown, Sylvia E.; Wu, He; Dongchen, Wenhua; Li, Yunbin; Lin, Chun; Liu, Zhengjie; Mao, Zichao (Frontiers in Plant Science, 2025)
IntroductionHydroxy-3-methylglutaryl-coenzyme A reductase (HMGR) is a key enzyme in the terpenoid biosynthetic pathway, playing a crucial role in plant stress responses. However, the HMGR gene family in Asparagus taliensis, a traditional Chinese medicinal herb with high steroidal saponin content and strong stress tolerance, remains poorly understood. This study investigates the stress response mechanisms of the HMGR gene family in A. taliensis under abiotic stress conditions.MethodsA comprehensive genome-wide analysis of the HMGR gene family in A. taliensis was conducted. The analysis included chromosomal localization, phylogenetic tree construction, linear analysis, gene structure characterization, motif distribution, cis-acting elements, and protein structure. Candidate AtaHMGR10 gene were overexpressed in Arabidopsis thaliana to analyze phenotypic changes under osmotic and salt stress, including seed germination rate and primary root length. Physiological parameters were also analyzed, and gene expression was validated using qPCR under drought, osmotic, and salt stress conditions.ResultsA total of 18 HMGR gene family members were identified in A. taliensis. The functions and evolution of AtaHMGR genes are conserved. AtaHMGR10 was selected as a promising candidate due to its unique expression profile. Docking analysis revealed that AtaHMGR10 has conserved motifs for binding both HMG-CoA and NADPH/NADH, showing equal affinity for both. Overexpression of AtaHMGR10 in transgenic A. thaliana enhanced tolerance to abiotic stresses, as evidenced by higher germination rates, improved primary root length, increased chlorophyll and proline levels, enhanced peroxidase (POD) and catalase (CAT) activities, and reduced malondialdehyde (MDA) content compared to non-transgenic plants under stress conditions.DiscussionThese findings highlight the role of AtaHMGR10 in enhancing plant stress tolerance, particularly in combating drought, osmotic, and salt stress. This understanding of its potential function provides avenues for improving crop resilience to abiotic stress through future gene modification.